TO STUDY THE HAEMOGLOBINOPATHIES AND RATIO OF COPPER AND ZINC IN SINDHI COMMUNITY OF BHOPAL - M. KAUR; C.B.S.DANGI; H. SINGH (International Journal of Pharma and Bio Sciences, 2013)
The genetic haemtological disorder such as beta–thalassaemia and sickle cell anaemia is one of the burning problems in India. The community wise study is of great help as it provides versatile information. A random cross-sectional study was conducted in 500 volunteers of Sindhi community belonging to all age groups and both sexes. The mass screening was done by help of NESTROFT, Sickling, Solubility and complete blood picture were performed on all samples along with BMI .Those positive for either one or both, screening tests were further analyzed for HbA2 by HPLC D-10. 120 positive cases of haemoglobinopathies were further analyzed for copper /zinc ratio. 120 positive cases of haemoglobinopathies were having low level of zinc and high level of copper, the ratio of copper / zinc was high along with low BMI. The positive cases were having different clinical manifestations along with liver and heart diseases in some cases.